2016
DOI: 10.1371/journal.pone.0160916
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Behaviors, and Virological Characteristics of Hepatitis B Virus Infection in a Group of Men Who Have Sex with Men in Brazil: Results from a Respondent-Driven Sampling Survey

Abstract: BackgroundMen who have sex with men (MSM) are at increased risk of exposure to hepatitis B virus (HBV) compared with the general population. This study aims to assess the epidemiological and virological characteristics of HBV infection in a sample of MSM in Brazil, where data are scarce.MethodsA cross-sectional study was conducted among MSM in the City of Goiânia, Central Brazil, from March to November 2014, using Respondent-Driven Sampling (RDS). After signing the consent form, participants were interviewed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
4
16
0
1
Order By: Relevance
“…Specifically, the sexual mode of HIV transmission was dominant in the group with HIV mono-infection, and in those with HBV co-infection, while in patients with HCV co-infection the IVDU was the most prevalent one. These data confirm that HBV co-infection is more frequent in the population of MSM [36,37], and HCV in the population of IVDU [32,38], which might change the epidemiological situation in Serbia in the future. Unlike the beginning of the AIDS epidemic in Serbia, when the prevailing transmission of infection was through blood, especially IVDU [26], at the present time the prevailing mode of transmission is through sexual contacts, primarily homosexual [26].…”
Section: Discussionsupporting
confidence: 69%
“…Specifically, the sexual mode of HIV transmission was dominant in the group with HIV mono-infection, and in those with HBV co-infection, while in patients with HCV co-infection the IVDU was the most prevalent one. These data confirm that HBV co-infection is more frequent in the population of MSM [36,37], and HCV in the population of IVDU [32,38], which might change the epidemiological situation in Serbia in the future. Unlike the beginning of the AIDS epidemic in Serbia, when the prevailing transmission of infection was through blood, especially IVDU [26], at the present time the prevailing mode of transmission is through sexual contacts, primarily homosexual [26].…”
Section: Discussionsupporting
confidence: 69%
“…Concerning hepatitis B, though the prevalence of lifetime HBV infection suggests a low HBV endemicity among the sugarcane cutters investigated, it should be emphasized this prevalence was slightly higher than that estimated in the urban population (20 to 69 year) from the Midwest (12.4%; 95% CI: 11.1–14.3) and Northeast (12.1%; 95% CI: 10.5–13.9) regions of Brazil [ 24 ]. On the other hand, this prevalence was similar to that reported recently in populations at risk for STIs, such as sex workers (17.1%; 95% CI: 11.6–23.4) [ 25 ] and men who have sex with men (MSM) (15.4%; 95% CI: 8.7–25.8) in Goiás [ 26 ]. In addition, seven individuals were HBsAg positive, being therefore potential disseminators of HBV.…”
Section: Discussionsupporting
confidence: 87%
“…That is why majority of epidemiological studies found association between increased age of participants and HBV infection. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%